Gut microbiota profiles in feces and paired tumor and non-tumor tissues from Colorectal Cancer patients. Relationship to the Body Mass Index. - Sofía Tesolato; Adriana Ortega-Hernández; Dulcenombre Gómez-Garre; Paula Claver; Carmen De Juan; Sofía De la Serna; Mateo Paz; Inmaculada Domínguez-Serrano; Jana Dziakova; Daniel Rivera; Antonio Torres; Pilar Iniesta (PLoS ONE, 2023)
Colorectal Cancer (CRC) and Obesity constitute two of the most common malignancies in the western world, and previously have been associated with intestinal microbial composition alterations. Our main aim in this study is to provide molecular data on intestinal microbiota patterns in subjects with CRC, as well as to establish possible associations with their Body Mass Index (BMI). A total of 113 samples from 45 subjects were collected and submitted to metagenomics analysis for gut microbiota. This study was performed by 16S ribosomal RNA bacterial gene amplification and sequencing using the Ion Torrent™ technology. The same dominant phyla were observed in feces and colorectal tissues, although a greater proportion of Fusobacteriota was found in tumor samples. Moreover, at the genus level, LEfSe analysis allowed us to detect a significant increase in Fusobacterium and Streptococcus in colorectal tissues with respect to fecal samples, with a significant preponderance of Fusobacterium in tumor tissues. Also, our data revealed relevant associations between gut microbiota composition and tumor location. When comparing bacterial profiles between right and left colon cancers, those from the left-sided colon showed a significant preponderance, among others, of the order Staphylococcales. Moreover, phyla Firmicutes and Spirochaetota were more abundant in the group of right-sided CRCs and phylum Proteobacteria was increased in rectal cancers. In relation to BMI of patients, we detected significant differences in beta diversity between the normal weight and the obese groups of cases. Microbiota from obese patients was significantly enriched, among others, in Bacteroidales. Therefore, our results are useful in the molecular characterization of CRC in obese and non-obese patients, with a clear impact on the establishment of diagnostic and prognosis of CRC.